The UK consensus supporting effective introduction of novel treatments for multiple myeloma in the National Health Service - Rakesh Popat; Supratik Basu; Sarah Henshaw; Kamaraj Karunanithi; Karthik Ramasamy; Inderjit Singh; Anish Tailor; Ian Walker; Tim Warren; Noreen Ali; Charles Duffield; Gordon Cook (eJHaem)
Abstract Introduction Multiple myeloma (MM) is a relapsing, debilitating blood cancer which remains incurable despite advances in treatments. Patients typically receive multiple lines of treatment, to which they become refractory, thereby limiting treatment options. B‐cell maturation antigen (BCMA) bispecific antibodies (BsAbs) represent a novel modality of treatment that has significant efficacy for relapsed or refractory patients. The objective was to develop consensus statements for the effective implementation of BCMA BsAbs for relapsed or refractory MM patients within the National Health Service (NHS). Methods The process employed a modified Delphi methodology. In March 2023, a literature review on the topic of novel treatments for MM was performed using the PubMed database. The process employed a modified Delphi methodology. Following a literature review, a steering group of eight expert clinicians identified and agreed on five main topics of focus and 44 statements. These were then developed into an online survey which was distributed to healthcare professionals working in Levels 1, 2 and 3 haematology centres in the United Kingdom. Results were then shared with the expert panel to determine conclusions. The threshold for consensus agreement was set at 75%. Results A total of 60 responses were received from all three centre levels. There was representation from all targeted centres. Consensus was achieved in 42 statements (95%) across three broad areas: the patient profile, initiation and step‐up dosing, monitoring and ongoing care, the role of multidisciplinary team and service designs for optimal management, consensus was not achieved for two statements. Given the level of agreement and that the stopping criteria were met, it was decided not to undertake further Delphi rounds. Conclusion This consensus provides a framework to support the effective introduction of novel treatments for MM in the NHS. The results were used to inform a checklist for use within haematology services when considering the provision of MM care specific to BCMA BsAbs.